Evaluasi Asesmen Sumatif Kelas Akhir (ASKA) pada Mata Pelajaran Projek Kreatif dan Kewirausahaan melalui Analisis Butir Soal Berbasis Anates Kelas XII Pemasaran - Vella Anggresta; Fera Shiami (Universitas Negeri Padang, 2026)
This study aims to examine the quality of the Final School Examination instrument in the subject of Creative Projects and Entrepreneurship (Projek Kreatif dan Kewirausahaan/PKK). The study employed a descriptive quantitative approach. There were 21 twelfth-grade students from the Marketing specialization program at SMK PGRI 15 Jakarta participated in this study. Data were collected through documentation of students answer containing 45 multiple-choice questions. The data were analyzed by using item analysis of Classical Test Theory using the Anates application including validity, reliability, difficulty level, discrimination power, and distractor quality. The results of the analysis indicate that most of the test items met the validity criteria (68.9%), although a proportion of the items were still invalid (31.1%). The instrument demonstrated very high reliability (0.95); however, the distribution of difficulty levels was dominated by easy and very easy categories (77.7%), making it less capable of comprehensively measuring students’ abilities. In addition, the discrimination power of several items was still low, and the distractor quality analysis showed that some answer options did not function optimally. These findings suggest that although the instrument is consistent, the quality of item construction has not yet been evenly developed.